1993
DOI: 10.1149/1.2220844
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Conductive Polymers: XIV . In Situ Spectroelectrochemical and Kinetic Studies on Poly(3‐Methylthiophene) Growth

Abstract: The growth mechanism of poly(3-methylthiophene) has been studied employing in situ spectroelectrochemical and kinetic measurements. Results indicate that: (i) the polymer film grows only when 3-methylthiophene is oxidized, suggesting that the radical-radical coupling reaction is important for the polymer growth; (ii) concentrations of intermediate species, i.e., radical cations of the trimer and tetramer, are maintained at a steady-state level during the growth; and (iii) both monomer and polymer concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…As a result, the probability of forming an ion pair of the oligomer +× species and the anion drops and, correspondingly, transfer of the oligomer radical-cations generated into the solution bulk decreases. On the whole, these results indicate the specific transfer of charged oligomers into the solution, which is in accord with the findings of Haier [8]. On the other hand, the subsequent transformations of these products indeed lead to the appearance of oligomers in solution, which, as shown by Correia [12], diffuse toward the anode and participate in the polymerization reaction, reducing its overvoltage.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…As a result, the probability of forming an ion pair of the oligomer +× species and the anion drops and, correspondingly, transfer of the oligomer radical-cations generated into the solution bulk decreases. On the whole, these results indicate the specific transfer of charged oligomers into the solution, which is in accord with the findings of Haier [8]. On the other hand, the subsequent transformations of these products indeed lead to the appearance of oligomers in solution, which, as shown by Correia [12], diffuse toward the anode and participate in the polymerization reaction, reducing its overvoltage.…”
Section: Resultssupporting
confidence: 88%
“…1) with those for charged and neutral oligomers of unsubstituted and substituted thiophene [8]. Haier [8] has found that, depending on the environment and substituents, the radical-cations of the thiophene dimer, trimer, and tetramer display absorption maxima at~400-425,~530-557, and 614-648 nm, respectively. Hence, the strongest band with maximum at 530 nm in the spectra of the soluble polymerization products (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the polymer morphology and structure depend on polymerisation route [9,10]. For successful metal recovery it is important to obtain polymer with a large surface area.…”
Section: Introductionmentioning
confidence: 99%